PEMANFAATAN LIMBAH ORGANIK MENJADI ECOPILLOW DI SEKOLAH MENENGAH PERTAMA KULON PROGO YOGYAKARTA - erwin kusumastuti kusumastuti; Sofyan Dwi Nugroho; Gyska Indah Harya (Jurnal Agro Dedikasi Masyarakat (JADM), 2024)
Coconut fiber is often just piled up and burned because it is often considered waste. Coconut fiber is an organic waste that is easily decomposed. This waste is still used by several sub-districts in Kulonprogo Regency where it is processed into materials for making products including coir rope, cocopot, brooms, doormats, and cocopeat which we often encounter in cleaning equipment shops and plant shops. This phenomenon provides strong creativity in upgrading innovations by increasing the added value of coconut fiber. The objectives of this training were deliberately given to Kulon Progo Middle School students, including knowing how to use coconut fiber waste in useful products training in making environmentally friendly health pillows; and knowing the convenience of using health pillows from coconut fiber waste. The method used in this training goes through several stages, namely processing coconut fiber waste which consists of preparing the material, separating, bleaching, and drying. Furthermore, coconut fiber which has gone through a processing process produces cocofiber which is ready to be used as a pillow-filling material. Coconut fiber has a higher fiber content compared to other fibers. This level of fiber has great potential as a substitute for pillow filling. Processing coconut shell waste as a pillow filling material is an alternative to reduce coconut shell waste, which until now has not been seen as having a high selling value by the public. Based on the results of a survey of 40 residents, 100% stated that pillow products made from coconut fiber have a good appearance and are comfortable when used so that sleep is quality.AbstractCoconut fiber is often just piled up and burned because it is often considered waste. Coconut fiber is an organic waste that is easily decomposed. This waste is still used by several sub-districts in Kulonprogo Regency where it is processed into materials for making products including coir rope, cocopot, brooms, doormats, and cocopeat which we often encounter in cleaning equipment shops and plant shops. This phenomenon provides strong creativity in upgrading innovations by increasing the added value of coconut fiber. The objectives of this training were deliberately given to Kulon Progo Middle School students, including knowing how to use coconut fiber waste in useful products training in making environmentally friendly health pillows; and knowing the convenience of using health pillows from coconut fiber waste. The method used in this training goes through several stages, namely processing coconut fiber waste which consists of preparing the material, separating, bleaching, and drying. Furthermore, coconut fiber which has gone through a processing process produces coco fiber which is ready to be used as a pillow-filling material. Coconut fiber has a higher fiber content compared to other fibers. This level of fiber has great potential as a substitute for pillow filling. Processing coconut shell waste as a pillow filling material is an alternative to reduce coconut shell waste, which until now has not been seen as having a high selling value by the public. Based on the results of a survey of 40 residents, 100% stated that pillow products made from coconut fiber have a good appearance and are comfortable when used so that sleep is quality.